Isolation of elusive HAsAsH in a crystalline diuranium(IV) complex - Gardner, Benedict M.; Balázs, Gábor; Scheer, Manfred; Wooles, Ashley J.; Tuna, Floriana; McInnes, Eric J.L.; McMaster, Jonathan; Lewis, William; Blake, Alexander J.; Liddle, Stephen T. (Wiley-VCH Verlag, 2015)
The HAsAsH molecule has hitherto only been proposed tentatively as a short-lived species generated in electrochemical or microwave-plasma experiments. After two centuries of inconclusive or disproven claims of HAsAsH formation in the condensed phase, we report the isolation and structural authentication of HAsAsH in the diuranium(IV) complex [{U(TrenTIPS)}2(μ-η2:η2-As2H2)] (3, TrenTIPS=N(CH2CH2NSiPri3)3; Pri=CH(CH3)2). Complex 3 was prepared by deprotonation and oxidative homocoupling of an arsenide precursor. Characterization and computational data are consistent with back-bonding-type interactions from uranium to the HAsAsH π*-orbital. This experimentally confirms the theoretically predicted excellent π-acceptor character of HAsAsH, and is tantamount to full reduction to the diarsane-1,2-diide form.